2022
DOI: 10.1055/s-0042-1755573
|View full text |Cite
|
Sign up to set email alerts
|

Massive Embolism: Knife versus PCI

Abstract: Pulmonary embolism is the third most common cardiovascular syndrome with an estimated up to 25% of patients presenting with sudden death. For those who survive, a mainstay of management for patients with hemodynamic stability is anticoagulation; however, recommendations and options are rapidly changing for patients with submassive or massive pulmonary embolism with hemodynamic instability. Catheter-based and surgical approaches offer efficacious management options for unstable patients or patients with contrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…24 As noted by Tohme et al, PE patients with a history of malignancy have a considerably higher mortality than those without a history of malignancy, and thus patients with widespread malignancy may not be considered for ECMO. 5 As previously noted in the study by George et al, serum lactate level >6 mmol/L at presentation may suggest futility of the use of ECMO. 20 V-A ECMO is associated with high rates of major complications including infection, bleeding, stroke, and limb ischemia, providing daily challenges to the ECMO team.…”
Section: Limitations In the Use Of Ecmo For High-risk Pementioning
confidence: 73%
See 2 more Smart Citations
“…24 As noted by Tohme et al, PE patients with a history of malignancy have a considerably higher mortality than those without a history of malignancy, and thus patients with widespread malignancy may not be considered for ECMO. 5 As previously noted in the study by George et al, serum lactate level >6 mmol/L at presentation may suggest futility of the use of ECMO. 20 V-A ECMO is associated with high rates of major complications including infection, bleeding, stroke, and limb ischemia, providing daily challenges to the ECMO team.…”
Section: Limitations In the Use Of Ecmo For High-risk Pementioning
confidence: 73%
“…1 In searching for strategies that may make a dent on this dismal mortality rate, investigators have, in the last decade, shown renewed interest in the potential beneficial role of venoarterial (V-A) extracorporeal membrane oxygenation (ECMO) in the treatment of patients with high-risk PE and, in particular, those with circulatory collapse or cardiac arrest. [2][3][4][5][6][7][8][9][10][11] In this review, we outline the mechanism, design, and operation of the V-A ECMO system; provide a brief overview of the historical background of this treatment modality; and discuss current and future applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation